Differences in morphological characteristics between female volleyball national team of Montenegro and Kosovo - Bojanic, D.; Ljubojevic, M.; Krivokapic, D.; Nokic, A.; Mekic, A. (Kinesiologia Slovenica, 2022)
The aim of this research was to determine the differences related to morphological characteristics and body composition among female players of Montenegro national junior volleyball team and Kosovo national junior volleyball team. A sample of the subject consists of a total of 25 top-level female junior players who were members of two national teams, participants of the European Championship qualifying 2020. The first sub-sample of the subjects consisted of 13 players of National team of Montenegro, of the average age 17.13 ± 0.54, while the other sub-sample consisted of 12 players of National team of Kosovo, of the average age of 16.35 ± 0.41. Anthropometric characteristics in the body composition were evaluated by a battery of 11 variables: body height (cm), body weight (kg), triceps skinfold (mm), back skinfold, biceps skinfold, abdominal skinfold, thigh skinfold, calf skinfold, body mass index (BMI), percentage of fat (%) and muscle mass (kg). Statistically significant differences (p<0.05) between body composition and morphological characteristic of the female volleyball players of two national teams, Montenegro and Kosovo, were determined by using a discriminatory parametric procedure with t-test for small independent samples. The results showed that the female volleyball players of Montenegro are somewhat higher, also they have greater body mass index, greater muscle mass and a significantly lower percentage of fat, compared to the female volleyball players of Kosovo. When it comes to variables of skinfolds, it was demonstrated only one statistical significance in favor of the Montenegrin National team, variable skinfold thigh.